2020
DOI: 10.3390/ijerph17103740
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Anxiety in Hong Kong during COVID-19

Abstract: It has been three months since the first confirmed case of coronavirus disease 2019 (COVID-19) in Hong Kong, and people now have a more complete picture of the extent of the pandemic. Therefore, it is time to evaluate the impacts of COVID-19 on mental health. The current population-based study aimed to evaluate the depression and anxiety of people in Hong Kong during the COVID-19 pandemic. Respondents were randomly recruited and asked to complete a structured questionnaire, including the patient health questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

53
673
20
40

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 757 publications
(786 citation statements)
references
References 41 publications
53
673
20
40
Order By: Relevance
“…Early evidence from China suggests that, during the pandemic, the general public has reported elevated symptoms of anxiety, depression [ 2 , 3 ], stress [ 3 ] and increased psychological distress [ 4 ]. For example, a Hong Kong study showed that 19% of participants met the criteria for a depressive disorder, and 14% for an anxiety disorder [ 5 ]. Longitudinal evidence shows that since the pandemic began, individuals have reported greater emotional distress [ 6 ], more negative effects, as well as higher symptoms of depression and anxiety [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early evidence from China suggests that, during the pandemic, the general public has reported elevated symptoms of anxiety, depression [ 2 , 3 ], stress [ 3 ] and increased psychological distress [ 4 ]. For example, a Hong Kong study showed that 19% of participants met the criteria for a depressive disorder, and 14% for an anxiety disorder [ 5 ]. Longitudinal evidence shows that since the pandemic began, individuals have reported greater emotional distress [ 6 ], more negative effects, as well as higher symptoms of depression and anxiety [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal evidence shows that since the pandemic began, individuals have reported greater emotional distress [ 6 ], more negative effects, as well as higher symptoms of depression and anxiety [ 7 ]. When asked retrospectively, 25.4% of the Chinese general public reported feeling that their mental health had deteriorated since the pandemic began [ 5 ]. Elevated mental health problems are also present among adults in the United Kingdom [ 8 ], Spanish university students and staff [ 9 ] and adults in the United States, where 43.3% reported high levels of depression and 45.4% reported high levels of anxiety [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the fast transmission of the virus between humans, high mortality rates and strict prevention measures including travel bans, home con nements, social distancing, compulsory face mask wear, school suspensions, this time of global crisis is characterized with strong negative emotions and deteriorated mental health. Several studies reported the heightened negative affectivity symptoms due to the pandemic (Limcaoco et al, 2020) and documented that COVID-19 pandemic exacerbated mental health issues including depression across the world (Bäuerle et al, 2020;Choi, Hui & Wan, 2020;Nickell et al, 2004;Tsang, Scudds, & Chan, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is known that there is a strong relationship between depression and noncompliance 10 . Patients were constantly at home during this pandemic, and this social isolation may lead to anxiety and depression 11 . Additionally, the anxiety that the disease has caused may affect dialysis treatment compliance.…”
Section: Introductionmentioning
confidence: 99%